War photography: between beauty and chaos - Serva, Leão (2017)
This book accuses The New York Times of glamorizing the war when editing photographs of confiict with strong aesthetic effect. The selection of images privileges bucolic scenes and emotional appeal to expose what the author considers to be an ideological distortion of the violence of US military intervention in Afghanistan and Iraq. At the same time, in isolating the photographs from the journalistic environment, the work radicalizes the aestheticizing effect and becomes, itself, a beautiful anthology.